Market potential analysis of selected fish products in Southern Mindanao - Carillo, Maria Jinsel P.
The study was done to analyze the market potential analysis of selected fish products in Southern Mindanao, namely: '"bangus," "tilapia," and "sugpo." This was done to identify market opportunities for the said fish in Region XI. A secondary data analysis was conducted, as well as interview of key informants in the market. The secondary data were gathered from the Bureau of Agricultural Statistics (BAS), the Bureau of Aquatic Resources (BFAR), and the National Statistics Coordinating Board (NSCB). Moreover, Internet sites such as the Philippine Institute for Development Studies (PIDS) Online Database supplemented the needed data- The study looked into the market potential by examining the relationship among the factors that influenced the quantity demanded of the said fish products. The income elasticity of demand, the own-price elasticity and the cross-price elasticity of the said fish products were also computed. The computed income elasticity of demand for "bangus" and "sugpo" 9.08 and 12.12, respectively. These indicate that the two fish products have potentials in the Southern Mindanao market.